2019
DOI: 10.1111/trf.15448
|View full text |Cite
|
Sign up to set email alerts
|

Iron status and risk factors for iron depletion in a racially/ethnically diverse blood donor population

Abstract: I ron depletion (ID) is common in blood donors, with estimated prevalence of intermediate ID (ferritin <26 ng/mL) of 33% to 40% in United States and Canadian donors. 1,2 Other jurisdictions have also found high rates of ID in their donor populations. [3][4][5] No US blood center uniformly tests the iron status of all donors and little systematic testing is performed elsewhere, 6,7 but donor age, sex, and donation frequency are routinely documented risk factors for ID. [2][3][4][5][8][9][10][11] Iron deficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 29 publications
2
32
0
1
Order By: Relevance
“…Definitive conclusions cannot be made, however, as the data are limited by the accuracy of self‐reported iron use. Regardless of the dosing frequency, essentially all donors will benefit from oral iron supplements . It is important to emphasize iron is most effective in the 4 to 8 weeks immediately following donation, when its absorption is greatest …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Definitive conclusions cannot be made, however, as the data are limited by the accuracy of self‐reported iron use. Regardless of the dosing frequency, essentially all donors will benefit from oral iron supplements . It is important to emphasize iron is most effective in the 4 to 8 weeks immediately following donation, when its absorption is greatest …”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the dosing frequency, essentially all donors will benefit from oral iron supplements. 33,34 It is important to emphasize iron is most effective in the 4 to 8 weeks immediately following donation, when its absorption is greatest. 35 Cigarette smoking is associated with increased hemoglobin in the general public, 36 first-time blood donors, 37 and high-intensity blood donors.…”
Section: Discussionmentioning
confidence: 99%
“…Iron depletion is common in blood donors, with estimated prevalence of low ferritin (LF; ≤26 ng/mL) ranging from 33% to 40% in US and Canadian donors subject to similar eligibility criteria . Other countries have also documented frequent iron depletion, and risk factors reported from most studies include young donor age, female sex, and regular blood donation .…”
mentioning
confidence: 99%
“…I ron depletion is common in blood donors, with estimated prevalence of low ferritin (LF; ≤26 ng/mL) ranging from 33% to 40% in US and Canadian donors subject to similar eligibility criteria. [1][2][3] Other countries have also documented frequent iron depletion, 4,5 and risk factors reported from most studies include young donor age, female sex, and regular blood donation. [2][3][4][6][7][8][9] Though regulatory interest and communications from the AABB (providing blood collector accreditation in the United States and internationally) have focused on whole blood donors, 10,11 a number of recent, mostly pilot studies have shown plateletpheresis donors to have elevated risk for iron depletion.…”
mentioning
confidence: 99%
See 1 more Smart Citation